(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The financial structures that make use of money flow for “easy money” or cheating purpose are called financial pyramids. Recently financial pyramids intensively penetrates IT area. It is rather suitable way of the fraud. Money flow modeling and activity analysis of such financial systems allows identifying financial pyramids and taking necessary means of precautions. In the other hand even investing companies that function normally when market conditions changes (e.g. interest rates) eventually might become financial pyramid. Modeling of financial pyramids allows identifying signs of such instability.